Effects of Levetiracetam Drug an Magnesium on Hematological Parameter and some Biochemical Parameters in White Rats - Shaimaa J. Al Sabaagh, Hanaa E. Mahood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective :The current study aimed to study the role of magnesium in reducing the effect of the Levetiracetam at a dose (25 mg/kg body weight) on hematological parameter and renal functions in White Rats. Materials and Methods: Thirty two adult male rats of160 -170 grams weight were adopted. Rats randomly allocated in to four groups ;control ,Levetiracetam 25 mg ,Levetiracetam25 mg with magnesium(Mg+2)100mg and the four group Levetiracetam25 mg with magnesium(Mg+2)150mg .all groups were dosed daily for one month . Results: the results revealed that levetiracetam causes significant decrease in hematological parameter(RBC, Hb , pcv)and significant elevations in WBC count ,and its causes significant elevations in renal urea and creatine comparing among the treatment groups with the control at (p≤0.05) . The magnesium show demonstrated beneficial effects on hematological parameters renal functions in the present study.